2022
DOI: 10.1111/cas.15532
|View full text |Cite
|
Sign up to set email alerts
|

ICAM1 promotes bone metastasis via integrin‐mediated TGF‐β/EMT signaling in triple‐negative breast cancer

Abstract: Bone‐related events caused by breast cancer bone metastasis substantially compromise the survival and quality of life of patients. Because triple‐negative breast cancer (TNBC) lacks hormone receptors and Her2‐targeted therapeutic options, progress in the treatment of TNBC bone metastasis has been very slow. Intercellular adhesion molecule 1 (ICAM1) is highly expressed in various cancers and plays an important role in tumorigenesis and metastasis. However, the effect and mechanism of ICAM1 in TNBC bone metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…In triple negative breast cancer (TNBC), the ICAM1 antibody significantly reduced cell migration and ICAM1 could act as a molecular target for TNBC [ 23 ]. A recent study reported that ICAM1 bound with integrins to activate the epithelial-to-mesenchymal transition process through TGF-β/SMAD signaling, ultimately enhancing breast cancer cell invasion [ 65 ]. Consistent with previous studies, our study found that ICAM1 could promote breast cancer cells local invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In triple negative breast cancer (TNBC), the ICAM1 antibody significantly reduced cell migration and ICAM1 could act as a molecular target for TNBC [ 23 ]. A recent study reported that ICAM1 bound with integrins to activate the epithelial-to-mesenchymal transition process through TGF-β/SMAD signaling, ultimately enhancing breast cancer cell invasion [ 65 ]. Consistent with previous studies, our study found that ICAM1 could promote breast cancer cells local invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Reprogramming processes, such as EMT, also play an important role. For example, Chen et al found that after interacting with integrins, intercellular adhesion molecule 1 caused tumor cells to undergo EMT via TGF-β/SMAD signaling, after which the cells’ mesenchymal properties facilitated tumor cell metastasis through blood circulation [85] . Furthermore, because BC cells’ exosomes disrupt bone remodeling in the BM process, they may effectively serve as drug carriers for treating MBCB [86] , [87] .…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular adhesion molecule 1 (ICAM1) is an important regulator of tumorigenesis and metastasis. Multiple integrin receptors (integrin α 2 , α L , α M , α V , β 2 , β 6 ) were shown to mediate the process by which ICAM1 promotes bone metastasis in breast cancer through TGF-β/SMAD/epithelial-to-mesenchymal transition signaling [ 131 ].…”
Section: Integrins Are Participants and Therapeutic Targets In Bone M...mentioning
confidence: 99%